Analisis usaha dan pemasaran Benur Udang Windu (Penaeus monodon) di UPTD. SPAPAL Manggar Kota Balikpapan Provinsi Kalimantan Timur - Atha, Adam Fawwaz; Abdusysyahid, Said; Ningsih, Etik Sulistiowati (Universitas Halu Oleo, 2023)
Tiger prawns are a superior commodity in Indonesia. The high demand for tiger prawns also influences the demand for tiger prawn fry. To be able to meet the need for tiger prawn fry, hatcheries have been established, one example of which is UPTD. SPAPAL Manggar. The increase in marketing demand has encouraged marketing activities at UPTD.SPAPAL Manggar by involving several marketing institutions. This research aims to determine marketing channels and institutions, margins, marketing efficiency, and business feasibility using the R/C Ratio indicator. This activity will be carried out at UPTD.SPAPAL Manggar in March 2023. This research is quantitative research with primary data and secondary data. The sampling technique used was the Purposive sampling method and Snowball sampling with the number of respondents in this study being 3 people. The results of this research show that there are 2 marketing channels, namely level 0 marketing channels and level 1 marketing channels with the marketing institutions involved being retailers. Marketing margins are found at retailers with an average of IDR 5-/head. The most efficient marketing channel is UPTD.SPAPAL Manggar at 1.24%, while for retailers the average is 5.57%. The business and marketing of tiger prawn fry at UPTD.SPAPAL Manggar is said to be profitable and feasible to run, because the R/C Ratio value of 2.75 is greater than > 1.